Ethics and situational crime prevention - Petersen, Thomas Søbirk (Routledge research in applied ethics, 2025)
"This book addresses the ethics of situational crime prevention (SCP). It seeks not only to analyse specific SCP strategies, but to demonstrate how ethical analysis can support and improve the implementation of SCP measures. In ethically analysing a particular SCP method, it is not enough to look at empirical data. Even if a method is effective at preventing crime, it may turn out to be ethically unattractive because it harms more people than it benefits, or because it violates our right to free movement. The book proceeds from the assumption that decision-making about whether we should use SCPs can only be conducted by carefully identifying, clarifying and critically evaluating the ethical arguments for and against use of the SCP method in question. The author analyses several SCP strategies that have not been treated in detail in the criminology or applied ethics literatures. These SCP strategies include gated communities, excluding people with a criminal record from housing or employment, enhanced surveillance and lighting in public and private spaces, and the implementation of intelligent speed adaption in vehicles. Ethics and Situational Crime Prevention is an essential resource for criminologists, moral philosophers, legal scholars, and social scientists with an interest in crime prevention"--